Multinational Association of Supportive Care in Cancer (MASCC) expert opinion / guidance on the use of clinically-assisted hydration in patients with advanced cancer - Davies, Andrew (My University, 2024)
Purpose: The provision of clinically assisted hydration (CAH) in patients with advanced cancer is controversial, and there is a paucity of specific guidance and so a diversity in clinical practice. Consequently, the Palliative Care Study Group of the Multinational Association of Supportive Care in Cancer (MASCC) formed a sub-group to develop evidence-based guidance on the use of CAH in patients with advanced cancer. Methods: This guidance was developed in accordance with the MASCC Guidelines Policy. A search strategy for Medline was developed, and the Cochrane Database of Systematic Reviews and the Cochrane Central Register of Controlled Trials were explored for relevant reviews/trials, respectively. Results: Due to the paucity of evidence, the sub-group was not able to develop a prescribed guideline, but was able to generate a number of "expert opinion statements": these statements relate to assessment of patients, indications for CAH, contraindications for CAH, procedures for initiating CAH, and reassessment of patients. Conclusions: This guidance provides a framework for the use of CAH in advanced cancer, although every patient requires individualised management.
PUBLISHED
Keywords: Advanced cancer; Clinically assisted hydration; Neoplasms; Palliative care; Practice guideline; Cancer; Palliative Medicine